“Nowadays the house would be called a stately home”: Pastoral Relocations in Tom Stoppard’s Arcadia - John Bull (Sillages Critiques)
Tom Stoppard’s Arcadia has a narrative structure that works backwards and forwards through time, examining concepts of change across the whole spectrum of philosophy and the arts. This is most obviously represented by that which we never see: “the landscape outside [that] we are told, has undergone changes”. However, simultaneously, that which we do see throughout, the room in which the action is located, remains unaltered. Change and flux are confronted by continuity and consistency. In this paper, I will consider the ideological implications of this paradox in relation to the playwright’s use of pastoral models that date from the English Renaissance, and yet reconfigure models of earlier post-second war British theatre, models that – according to many critical accounts – had long been superseded and abandoned. Arcadia is a supposedly ideology-free zone that is actually constituted of disputed ideological discourses.